Methods of test for paints. Tests involving chemical examination of liquid paints and dried paint films. Determination of 'soluble' lead in the solid matter in liquid paints: method for use in conjunction with The Control of Lead at Work Regulations, 1980 (S.I. 1980 No. 1248) Part B3, (29th July 1983) - British Standards Institution,
No abstract available